Coca Cultivation in the Huallaga and VRAE: A Comparative Approach to Productive Systems and the Impact on Forests (1978-2003) - Bedoya Garland, Eduardo (2023)
Drawing on two studies and surveys carried out in the Upper Huallaga in 1981 and the VRAE in 2001, both located in the upper Peruvian amazon basin, this paper seeks to describe and analyze the historical and economic conditions under which coca cultivation for illicit purposes expanded in both regions. In this sense, it describes how this history shaped an inefficient and destructive migratory agriculture. Although the periods analyzed in each case are different, with a difference of twenty years between one and the other, the information we have is sufficiently valuable to establish a useful and valuable comparison. These are the two Amazonian regions that had the largest extension of coca plantations at the national level during the study period. When coca expanded in the Upper Huallaga, there was already a much more intense social and economic history of articulation with the market and modernity than in the VRAE. That is, although the contexts and socio-environmental histories of each basin were quite different, the similarities in productive strategies remained significant. Coca, as a plantation or permanent crop planted in relatively small areas, did not eliminate the shifting agriculture practiced by most Andean settlers in the high jungle. From time to time, coca growers abandoned their plantations in the phase of decreasing yields, in search of new lands and fertile soils within their own properties or in more distant areas, reproducing the slash-and-burn method.